Redox-Sensitive Glyoxalase 1 Up-Regulation Is Crucial for Protecting Human Lung Cells from Gold Nanoparticles Toxicity - Angela Gambelunghe; Stefano Giovagnoli; Alessandro Di Michele; Simona Boncompagni; Marco Dell'Omo; Kerstin Leopold; Ivo Iavicoli; Vincenzo Nicola Talesa; Cinzia Antognelli (MDPI AG, 2020)
Gold nanoparticles (AuNPs) are considered nontoxic upon acute exposure, at least when they are equal or above 5 nm size. However, the safeguard mechanisms contributing to maintain cell viability are scarcely explored so far. Here, we investigated the cyto-protective role of Glyoxalase 1 (Glo1), a key enzyme involved in the control of deleterious dicarbonyl stress, in two human cell types of the respiratory tract, after an acute exposure to AuNPs with a main size of 5 nm. We found that the redox sensitive Nrf-2-mediated up-regulation of Glo1 was crucial to protect cells from AuNPs-induced toxicity. However, cells challenged with a pro-inflammatory/pro-oxidative insult become susceptible to the pro-apoptotic effect of AuNPs. Notably, the surviving cells undergo epigenetic changes associated with the onset of a partial epithelial to mesenchymal transition (EMT) process (metastable phenotype), driven by the increase in dicarbonyl stress, consequent to Glo1 inactivation. As a physiological respiratory epithelium is required for the normal respiratory function, the knowledge of the protective mechanisms avoiding or (when challenged) promoting its modification/damage might provide insight into the genesis, and, most importantly, prevention of potential health effects that might occur in subjects exposed to AuNPs, through targeted surveillance programs, at least under specific influencing factors.